2008
DOI: 10.1016/j.jtcvs.2008.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in coronary anastomosis with cardiac surgery simulation

Abstract: In general, distributed practice with the task station resulted in improvement in the ability to perform an anastomosis, as assessed by times to completion and performance ratings, not only with the task station but also with the beating-heart model. Not all residents improved, which is consistent with a "ceiling effect" with the simulator and a "plateau effect" with the trainee. Simulation can be useful in preparing residents for coronary anastomosis and can provide an opportunity to identify the need and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 22 publications
2
116
0
2
Order By: Relevance
“…With an overall improvement in score of 0.77, trainees who performed poorly initially benefited the most from this exercise; notably, the bottom five participants improved 1.39 on a 5-point scale. This finding is consistent with previous studies that have shown that less experienced trainees (ie, those with lower initial scores) benefit more from low-fidelity simulator use than trainees with higher initial scores [9]. From an educational perspective, it is therefore important to identify those with less experience and to provide earlier skills training.…”
Section: Commentsupporting
confidence: 89%
See 2 more Smart Citations
“…With an overall improvement in score of 0.77, trainees who performed poorly initially benefited the most from this exercise; notably, the bottom five participants improved 1.39 on a 5-point scale. This finding is consistent with previous studies that have shown that less experienced trainees (ie, those with lower initial scores) benefit more from low-fidelity simulator use than trainees with higher initial scores [9]. From an educational perspective, it is therefore important to identify those with less experience and to provide earlier skills training.…”
Section: Commentsupporting
confidence: 89%
“…The assessment tool, which is based on a modified Objective Structured Assessment of Technical Skills (OSATS), included 12 component skills scored on a 5-point Likert scale (1 ¼ poor; 5 ¼ excellent), with descriptive anchors specific to each component [2,5,9,11]. Also, a pass-fail grade was given based on overall performance in executing the coronary anastomosis, as judged by the rater.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by a study by Fann and colleagues [9] demonstrating that trainees who used a coronary anastomosis simulator had decreased time to completion for an anastomosis and improved performance-rating scores. Simulation affords endless practice opportunities to refine skills, ability to learn from mistakes, and offers "permission to fail" in an environment that does not adversely affect patient care [10].…”
Section: Case Volumementioning
confidence: 69%
“…Biologic tissue Synthetic material Simulated tasks Tokuda and Song [9] No Yes Coronary artery anastomosis Izzat and colleagues [10] No Yes Coronary artery anastomosis Wilasrusmee and colleagues [13,14] Yes Yes Arterial-venous fistula with polytetrafluoroethylene (PTFE) Arterial-venous fistula creation in human patients Fann and colleagues [11] No Yes Coronary anastomosis (stationary and beating heart) Fann and colleagues [12] Yes Yes Coronary anastomosis 'Boot Camp' (stationary heart) Hance and colleagues [7] Yes Yes Femoral artery dissection Aortic cannulation Coronary artery bypass graft anastomosis Ramphal and colleagues [15,16] Yes No 'Skin-to-skin' simulated reality Coronary anastomosis (stationary and beating heart) Aortic valve replacement (prosthetic, homograft and pulmonary autograft) Sidhu and colleagues [8] Yes Yes Anastomosis of plastic graft to plastic tube or cadavaric brachial artery. Anastomosis of plastic graft to femoral artery of live pig.…”
Section: Authormentioning
confidence: 99%